2013
DOI: 10.1371/journal.pone.0054173
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Regulator Pax6 Is Essential for Maintenance of Islet Cell Function in the Adult Mouse Pancreas

Abstract: The transcription factor Pax6 is a developmental regulator with a crucial role in development of the eye, brain, and olfactory system. Pax6 is also required for correct development of the endocrine pancreas and specification of hormone producing endocrine cell types. Glucagon-producing cells are almost completely lost in Pax6-null embryos, and insulin-expressing beta and somatostatin-expressing delta cells are reduced. While the developmental role of Pax6 is well-established, investigation of a further role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 55 publications
8
66
0
Order By: Relevance
“…In immortalized β cell lines, PAX6 was shown to bind and activate the promoters of insulin and additional β cell genes (26,31). Deletion of Pax6 in adult murine islet cells causes hyperglycemia, with reduced expression of insulin, glucagon, and somatostatin and upregulated expression of ghrelin (32). A more recent study showed that deletion of Pax6 in adult α or β cells induces ghrelin expression in mutant cells (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In immortalized β cell lines, PAX6 was shown to bind and activate the promoters of insulin and additional β cell genes (26,31). Deletion of Pax6 in adult murine islet cells causes hyperglycemia, with reduced expression of insulin, glucagon, and somatostatin and upregulated expression of ghrelin (32). A more recent study showed that deletion of Pax6 in adult α or β cells induces ghrelin expression in mutant cells (33).…”
Section: Resultsmentioning
confidence: 99%
“…More work is needed to understand what determines whether a particular gene will be repressed or activated in β cells by PAX6 binding. Moreover, PAX6 is ubiquitously expressed in hormone-producing islet cells, and in each islet cell type, it is required for maintaining a particular identity, sometimes by controlling opposing genes and pathways in different cell types (26,32). The differential effects of PAX6 in different islet cell types likely involve cooperation with cell-type-specific factors or coregulators.…”
Section: Discussionmentioning
confidence: 99%
“…Pax6 is a transcription factor that is essential in the adult islet for maintenance of cell identity and function, suggesting that the reduced function in mTOR mutant islets is due, in part, to loss of Pax6 expression. Loss of Pax6 in the adult islet results in an increase in ghrelin and severe reductions in α, β and δ cells (Hart et al, 2013), a phenotype that mirrors a loss of mTOR in islets. Pax6 and mTOR mutants additionally share similar maturation and functional defects as measured by reductions in Mafa and Glut2 in β cells (Gosmain et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…3B). Pax6 has been shown to be essential for the maintenance of adult islets, while Nkx2.2 is known to regulate β-cell function (Doyle and Sussel, 2007;Hart et al, 2013;Sander et al, 1997). In addition, Nkx6.1 and Foxo1 transcription factors are known to regulate β-cell growth (Okada et al, 2007;Taylor et al, 2015).…”
Section: Maturation and Function Are Compromised In Mtor Mutant Isletsmentioning
confidence: 99%
“…Moreover, the G-protein-coupled receptor (GPCR)-regulated PAX6 activity in somatostatin transcription has not been characterised [23,25,26]. Knockdown of PAX6 significantly reduced isoprenaline-induced somatostatin transcription, suggesting an essential role for PAX6 in the stress response, in agreement with its functional importance in maintaining pancreatic cell-type specificity and pancreatic development [27][28][29][30] 361 and pS 398 in humans, respectively) are potential phosphorylation sites downstream of ERK [31]. However, only the phosphorylation of the S413 site shows functional relevance in the regulation of PAX6 transcriptional activity [31].…”
Section: Discussionmentioning
confidence: 99%